Sporting activity and drug use: alcohol, cigarette and cannabis use among elite student athletes. - Peretti-Watel P; Guagliardo V; Verger P; Pruvost J; Mignon P; Obadia Y (Addiction, 2003)
AIMS: To study the relationship between sporting activity and alcohol, cigarette and cannabis use among adolescents and young adults, by focusing on elite student athletes (ESAs). DESIGN, SETTING, SUBJECTS: Cross-sectional survey (Spring 2002), in a sample of 460 ESAs (ages 16-24 years) recruited at 40 public centres gathering the young sporting elite from 30 different sports in South-Eastern France, comparison with samples of the general population of adolescents in South-Eastern France. MEASURES: Respondents were asked confidentially by a self-administered questionnaire about their use of licit and illicit drugs, their sporting activity and other aspects of their life-style. FINDINGS: Prevalences of cigarette, alcohol and cannabis use were markedly lower for ESAs than for other adolescents (generally twice or three times as low). Among ESAs, when compared with the practice of an individual sport, the practice of a team sport was correlated positively with alcohol use (OR = 2.7 for girls, OR = 1.8 for boys), and the practice of a sliding sport was correlated positively with cannabis use (for girls: OR = 2.3) and with alcohol use (for boys: 4.3). Girls who entered competition at international level were more prone to smoke cigarettes and cannabis (OR = 6.1 and 2.4, respectively). CONCLUSIONS: As a whole, practising sports as an elite student-athlete can be considered as correlated negatively with cigarette, alcohol and cannabis use. Nevertheless, this relationship depends on the kind of sport practised as well as the level of competition, and further research is needed to understand specific elite athletes' motives for use.